2016
DOI: 10.1103/physrevb.93.054504
|View full text |Cite
|
Sign up to set email alerts
|

TopologicalD+p-wave superconductivity in Rashba systems

Abstract: We show two-dimensional "strong" topological superconductivity in d-wave superconductors (SCs). Although the topological invariant of the bulk wave function cannot be defined in d x 2 −y 2 -wave and dxy-wave SCs because of nodal excitations, the bulk energy spectrum of d-wave SCs on a substrate is fully gapped in a magnetic field. Then the superconducting state is specified by a nontrivial Chern number, and hence topologically nontrivial properties are robust against disorders and interactions. We discuss high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 78 publications
(133 reference statements)
2
46
0
Order By: Relevance
“…Note that g k = −g −k , and thus the Rashba coupling breaks inversion symmetry, but does not break time-reversal invariance; the Zeeman field h does, however. This is the arXiv:1807.02489v1 [cond-mat.supr-con] 6 Jul 2018 model adopted by Yoshida and Yanase [11]. In the presence of superconductivity, the mean-field, Bogoliubov-de Gennes Hamiltonian requires a doubling of the degrees of freedom in order to be expressed in the usual form:…”
Section: A Noninteracting Hamiltonianmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that g k = −g −k , and thus the Rashba coupling breaks inversion symmetry, but does not break time-reversal invariance; the Zeeman field h does, however. This is the arXiv:1807.02489v1 [cond-mat.supr-con] 6 Jul 2018 model adopted by Yoshida and Yanase [11]. In the presence of superconductivity, the mean-field, Bogoliubov-de Gennes Hamiltonian requires a doubling of the degrees of freedom in order to be expressed in the usual form:…”
Section: A Noninteracting Hamiltonianmentioning
confidence: 99%
“…On the other hand, a greater variety of triplet states is possible. We will probe the state studied by Yoshida and Yanase [11], in which the dvector takes the form d k = ∆ p (sin k y , sin k x , 0). This triplet gap function is chosen because it belongs to the same irreducible representation of the point group C 4v of the noninteracting Hamiltonian as the d-wave gap function, and thus can mix with it.…”
Section: A Noninteracting Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this paper is to explore all possible topologically non‐trivial non‐centrosymmetric superconducting states in graphene‐based materials by combining all the phenomena mentioned above, including the effects of intrinsic (KM) and the Rashba SO couplings, the mixture of d + id spin singlet and triplet p + ip ‐wave pairings in the presence of both KM and the Rashba SO couplings. A recent related study on the simplified model without KM interaction in cuprates has shown non‐trivial topological properties . However, there is still lack of a comprehensive analysis of the more general and generic model systems for NCS on honeycomb lattice.…”
Section: Introductionmentioning
confidence: 99%
“…13 Some other recent researches concerning topological superconductor include. 14,15 But, so far, it has been largely overlooked for the 2D TR breaking C 2 = −1 (class C in the Altland-Zirnbauer(AZ) classification 16,17 ) topological superconductors and for the 3D TR invariant class CI topological superconductors with T 2 = 1 and C 2 = −1. A few previous researches, by constructing theoretical models for simplest cases, include.…”
Section: Introductionmentioning
confidence: 99%